ADDITION OF TAPE YEAST IN RATING ON PRODUCTION PERFORMANCE OF LANDRACE PIG - I K. N., Ditama; Wibawa, A. A. P. P.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
This study aims to determine the effect of the addition of tape yeast on the performance of landrace pig production. The study was conducted in Tabanan regency and lasted seven weeks. The study used was a completely randomized design (CRD) consisting of four treatments, namely P0: Landrace pigs fed a diet without tape yeast as a control, P1: Landrace pigs fed a diet with the tape yeast 0.1%, P2: Landrace pigs fed with tape yeast 0.2%, P3: Landrace pigs fed a diet with the tape yeast 0.3%. Each treatment had 4 replications. Variables observed included ration consumption, final body weight, weight gain and Feed Conversion Ratio (FCR). Data were analyzed using variance. The results showed that the consumption of tape yeast feeding rations of 0.1% (P1) differed markedly (P<0.05) higher than that of landrace pigs without giving tape yeast (P0). Provision 0,3% tape yeast (P3) is the treatment with the highest final weight and weight gain compared to other treatments and statistically different real (P<0.05). Giving 0.3% (P3) tape yeast is the best treatment of other treatments and statistically real difference (P<0.05) lowers the Feed Convertion Ratio (FCR). Based on research, it was concluded that giving tape yeast given to landrace pigs can increase ration consumption in tepe yeast administration by 0.1%, while giving tape yeast by 0.3% can increase final weight and weight gain. In the administration of yeast by 0.3% can decrease FCR. Keyword: Saccharomyces spp. (tape yeast), probiotic, performance production, landrace pig